Pancreatic Tuberculosis or Autoimmune Pancreatitis - Ayesha Salahuddin; Muhammad Wasif Saif (Case Reports in Medicine)
Introduction. Isolated pancreatic and peripancreatic tuberculosis is a challenging diagnosis due to its rarity and variable presentation. Pancreatic tuberculosis can mimic pancreatic carcinoma. Similarly, autoimmune pancreatitis can appear as a focal lesion resembling pancreatic malignancy. Endoscopic ultrasound-guided fine needle aspiration provides an effective tool for differentiating between benign and malignant pancreatic lesions. The immune processes involved in immunoglobulin G4 related systemic diseases and tuberculosis appear to have some similarities. Case Report. We report a case of a 59-year-old Southeast Asian male who presented with fever, weight loss, and obstructive jaundice. CT scan revealed pancreatic mass and enlarged peripancreatic lymph nodes. Endoscopic ultrasound-guided fine needle aspiration confirmed the presence of mycobacterium tuberculosis. Patient also had high immunoglobulin G4 levels suggestive of autoimmune pancreatitis. He was started on antituberculosis medications and steroids. Clinically, he responded to treatment. Follow-up imaging showed findings suggestive of chronic pancreatitis. Discussion. Pancreatic tuberculosis and autoimmune pancreatitis can mimic pancreatic malignancy. Accurate diagnosis is imperative as unnecessary surgical intervention can be avoided. Endoscopic ultrasound-guided fine needle aspiration seems to be the diagnostic test of choice for pancreatic masses. Long-term follow-up is warranted in cases of chronic pancreatitis.